Tobacco use and its associated factors among undergraduate public health students in Kathmandu Valley. - Chand, Birendra (2021)
SUMMARY: Introduction: Tobacco use is one of the most important preventable risk factors for noncommunicable diseases. It has been seen that students have higher frequency of smoking compared to general population. This study was conducted to access the prevalence of tobacco use, second hand smoke, tobacco cessation behaviours and associated factors of tobacco use among undergraduate public health students in Kathmandu valley. Methods and materials: A web-based descriptive cross-sectional study was conducted among 341 undergraduate public health students. The WHO's GHPSS questionnaire was used through online survey approach. Non-probability convenience sampling technique was used to collect the data from students. Data were analysed by using SPSS 20. Results: The mean age of the participated students was 21.9 years (Std. Dev ±2.07). A total of 16.7% students were current cigarette smokers. 38.1% students had ever smoked cigarettes, and 62% had smoked first cigarettes during adolescence life. Cigarette smoking consumption was higher than the use of other tobacco products like chewing tobacco, snuff, bidis, hookah, cigar or pipes. The prevalence of second hand smoke was 17.6% and 40.2% at home and public places respectively. Out of 57 current smoker students, 31.5% of the students wanted to stop smoking now and 19.3% of the students tried to stop smoking cigarettes during past year. Smoking was found to be associated with age (OR: 1.930, 95% CI: 1.034-3.601, p=0.039), sex (OR: 0.062, 95% CI: 0.024- 0.159, p<0.001), family history of tobacco use (OR: 2.249, 95% CI: 1.264-4.003, p=0.007) and friend's tobacco using habit (OR: 17.50, 95% CI: 5.347-57.274, p<0.001) of the students. Other tobacco product consumption was not significantly associated with all the independent variables except sex of the students (OR: 0.349 95% CI: 0.171-0.71, p=0.004). Conclusion: There is a notable prevalence of smoking and second hand smoke among the public health students. Cigarette is the most commonly used tobacco product than any others form of tobacco. Further in-depth studies regarding smoking and second hand smoke assessment should be conducted. Key words: Tobacco use, second hand smoke, public health students, Nepal